The Quest For ‘sheltering Skies’ in Ghassan Kanafani’s Men in The Sun (1963) - Nadia Naar Gada (The Journal of Studies in Language, Culture and Society, 2024)
The present paper looks into Ghassan Kanafani's seminal work, Men in the Sun, initially published in Arabic as Rijal fi al-shams (1963), adapted into a film, entitled The Dupes in 1972, and translated into English in 1978, by examining the narrative’s close relationship with the quest theme, the loss of identity and search for belonging, as embodied by the characters in the novella. The study draws mainly on the theoretical framework of Northrop Frye as developed in his Anatomy of Criticism (1957). The theorist’s concept of the “tragic quest” with its main steps will guide our re-reading of Kanafani’s work in order to examine how the main characters embark on a daring journey, which primarily starts with their shift from Basra along their sufferings for survival across the scorching weather, and their downfall and death by perishing in the desert before reaching their destination, Kuwait. The intention is also to show how the characters’ ill- fated quest epitomizes the Palestinians’ collective sense of loss, their torments of living in camps far from Palestine, their poverty, displacement, and identity crisis.